IOP-lowering therapy and ocular surface in glaucoma. Part 2. The effect of preservatives on ocular surface - A.V. Antonova; V.P. Nikolaenko; V.V. Brzheskiy (РМЖ "Клиническая офтальмология")
IOP-lowering therapy and ocular surface in glaucoma. Part 2. The effect of preservatives on ocular surface A.V. Antonova1, V.P. Nikolaenko1,2, V.V. Brzheskiy3 1City Multidisciplinary Hospital No. 2, St. Petersburg, Russian Federation 2St. Petersburg State University, St. Petersburg, Russian Federation 3St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation This article reviews published data from different years (mainly recent data) on the effect of active ingredients and preservatives of IOP-lowering medications on ocular surface. The rate and severity of ocular surface diseases are directly associated with dosage regimen and duration of topical glaucoma treatment. Dose-dependent and time-dependent loss of goblet cells, expansion and activation of fibroblast populations, release of proinflammatory cytokines by conjunctival cells account for dry eye symptoms and signs, poor adherence to treatment, and poor results of glaucoma filtration surgery. However, the analysis of more than 16,000 PubMed publications using keywords “ocular surface” did not answer a number of important questions. Can ocular surface disease symptoms reduce following the surgery? Can ocular surface get back to its baseline anatomical functional state and provide long-term filtering bleb functioning? What is the maximum d uration of glaucoma pharmacotherapy to have a chance of ocular surface improvement after glaucoma surgery? The aim of our studies is to address these challenges. Keywords: glaucoma, glaucoma therapy, ocular surface, dry eye disease, OSDI, inflammation, preservatives, benzalkonium chloride, preservative-free agents. For citation: Antonova A.V., Nikolaenko V.P., Brzheskiy V.V. IOP-lowering therapy and ocular surface in glaucoma.  Part 2. The effect of preservatives on ocular surface. Russian Journal of Clinical Ophthalmology. 2020;20(3):133–141. DOI: 10.32364/2311-7729-2020-20-3-133-141.